Design and implementation of an adaptive web-based hypermedia learning system: A prototype - Mohd. Hashim, Siti Zaiton; Yusof, Norazah; Ahmad, Nor Bahiah (2001)
Nowadays, internet has become a significant medium for communication in every aspect of human's life including education. Academically, the impact is great that we are moving from real class room to virtual one. World Wide Web environment has a great potential to be a teaching and learning aids for all level of educations, ranging from primary schools to high institutions. It gives a good opportunity for the teachers to put all teaching materials to assist students to learn even outside class hours. However, this internet and hypermedia system has some drawbacks that can cause teaching and learning to be less effective due to its static links and non-linear nodes. One solution is to develop a dynamic environment which incorporates the features of hypermedia and intelligent tutoring system that allows user control and at the same time can adapt to user's ability. This paper aims to present the design and development of a prototype f an adaptive web-based learning system, called SPAtH for teaching and learning C programming on web, that will identify the student's performance based on certain criteria gathered by the student model such as his academic background, preferences and state of knowldge acquisition. This will in turn provide the student with suitable learning materials, exercises and questions appropriately. This paper also discusses AI techniques that can be used by the adaptive engine to make it more flexible and adaptive to the student's needs.